Prevalence and burden of oral complications in breast cancer: systematic literature review - Gómez Espinosa, Evelyn (2024)
Supplementary data are available at DOI: 10.24875/j. gamo.24000044. This material is provided by the corresponding author and posted online for the benefit of the reader. The content of the supplementary data is the sole responsibility of the authors.